Melastoma malabathricum L . natural preservatives business plan - Tengku Khamanur Azma, Tg. Mohd Zamri (2013)
KKE Enterprise was now preparing the Business Plan in order to introduce Melastoma malabathricum L. (MML) Natural Preservatives to the related industry. KKE Enterprise will apply special constructed natural preservative to inhibit the growth of microorganism that caused spoilage to the end products and at once to increase their shelf life. These products, called MML preservative (MMLP), have the ability to stop the activity of microbial such as B. cereus, B. subtilis, S. typhi, and E. coli. We will supply the complete dried powder at lower price.